Control Freaks: How Online and Mobile Communication is Reshaping Social Contact - Baron, Naomi Susan (Language at Work - Bridging Theory and Practice, 2009)
The year was 1956. At the time, the word “computer” referred to a roomful of hardware. “Telephones” were bulky black devices, tethered to walls (and, at least in the US, exclusively owned by the phone company). But a new gadget appeared on the scene that was destined to revolutionize our perceptions of technology – and our ability to manipulate it. The new contraption was a television remote control.